Penerapan Meteode Card Sort Untuk Meningkatkan Keaktifan Siswa Kelas V Pada Pelajaran Al-Qur’an Hadits - Alwan, Muhammad (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Abstract This study aims to increase student activity in the learning process. This research was designed using Classroom Action Research. The research instruments used in this research were observation sheets and field notes used to obtain data or information relating to class situations that were not listed in the observation sheets. In this study field notes were used to observe things that happened in the classroom during the application of the card learning method. sort. The results showed that in the first cycle the average student activity was in the inactive category with a value of 46.66%. Furthermore, in cycle II, the average student activity has shown the quite active category with a value of 60%, but in this cycle, improvements still need to be made so that researchers use cycle III. In cycle III, the average student activity has shown an active category of 80%. Thus, the Card Sort learning method can be recommended to teachers in carrying out learning.